2013
DOI: 10.1007/s10143-013-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of thalamic gliomas: case selection, technical considerations, and review of literature

Abstract: This study aimed to identify (1) the thalamic gliomas suitable for surgical resection and (2) the appropriate surgical approach based on their location and the displacement of the posterior limb of the internal capsule (PLIC). A retrospective study over a 5-year period (from 2006 to 2010) was performed in 41 patients with thalamic gliomas. The mean age of these patients was 20.4 years (range, 2-65 years). Twenty (49 %) tumors were thalamic, 19 (46 %) were thalamopeduncular, and 2 (5 %) were bilateral. The PLIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
3
34
1
Order By: Relevance
“…Regarding the radiological control, there was a statistical significance between lesion control and microsurgery in this study as p value = 0.03. This was agreed by Sai Kiran et al who concluded that radical resection results in the improvement of clinical condition as well as tumor control in majority of the patients with thalamic tumors [25].…”
Section: Discussionsupporting
confidence: 69%
“…Regarding the radiological control, there was a statistical significance between lesion control and microsurgery in this study as p value = 0.03. This was agreed by Sai Kiran et al who concluded that radical resection results in the improvement of clinical condition as well as tumor control in majority of the patients with thalamic tumors [25].…”
Section: Discussionsupporting
confidence: 69%
“…halamic tumors are relatively uncommon: they account for approximately 1%-5% of all brain tumors in children, 3,6,9,12,29,31,32,37 although differences in nomenclature and a limited number of exclusively pediatric series make it difficult to quantify. In the past, the outcome of surgical treatment for thalamic tumors was poor.…”
mentioning
confidence: 99%
“…This is not surprising if we consider that Krieg 21 . The PLIC can be easily localised by intraoperative subcortical mapping while pre-operative DTI of the CST can occasionally be difficult due to tumor infiltration of the white matter 23 .…”
Section: Discussionmentioning
confidence: 73%
“…In the literature, there are few publications which address this question. Some papers describe satisfactory results in the resection of grade I thalamic astrocytomas which most typically affect children 12,13,20,21 . Thus, in this category of patients the surgical indication to resection is generally clear.…”
Section: Discussionmentioning
confidence: 98%